Analysis of Full Duplex Relay to Maximize Performance in Cellular Network - Baik, Jong Soo; Kim, Jae Hyun (International Conference on ICT Convergence, 2020)
Full duplex (FD) communication is a spotlighted technology as a most promising solution that can solve channel capacity problem in unmanned aerial vehicle (UAV)-assisted cellular network. However, in the case of UAV communication using FD, there is a lack of research on how to improve the throughput of the communication area and cells. For these reasons, we analyze the throughput of the cellular network with FD UAV. The user equipment (UE) in the UAV coverage determines the relay according to the signal-to-interference plus noise ratio (SINR). As altitude of UAV and number of UAV increase, the simulation result show better throughput as coverage of UAV increase.
Keywords: Cellular network; Communication area; Full-duplex; Full-duplex relays; Signal to interference plus noise ratio; User equipments; Cellular network; Full duplex (FD); relay; Unmanned aerial vehicle (UAV)